Acupuncture for chronic nonpulsatile tinnitus: A randomized clinical trial - Bahram Naderinabi; Soheil Soltanipour; Shadman Nemati; Alia Saberi; Sepideh Parastesh (Babol University of Medical Sciences, 2018)
Background: There is challenge to find an effective treatment for tinnitus. Few studies were done on the effects of acupuncture on tinnitus. This study evaluated the effect of acupuncture on chronic non-pulsatile tinnitus. Methods: This randomized double-blind clinical trial was conducted from December 2014 to September 2015. Patients suffering from chronic non-pulsatile tinnitus were randomly allocated into two groups: acupuncture vs. placebo. They were treated in 15 sessions and at the end of the fifteenth sessions and 3 weeks after completion of the treatment, visual analog scale (VAS) for tinnitus loudness and tinnitus severity index (TSI) questionnaires were completed. Results: The case group included 26 males and 18 females, and in the control group there were 27 males and 17 females: with mean age of 49.11±1.07 and 55.20±8.33 years, respectively (p=0.005). TSI and VAS before treatment were 43.84±2.81 and 9.56±0.43 in cases and 43.52±2.94 and 9.54±0.45 in controls, respectively. Both measures improved after 15 sessions in cases to 24.82±1.04 and 2.88±0.33, and to 33.16±1.24 and 7.86±0.23 in controls. The changes of TSI and VAS were significant in all groups (p<0.001). TSI and VAS in acupuncture group were lower than placebo group in each session (p<0.001), except TSI in the tenth session (p=0.392). Conclusions: Acupuncture is effective in reducing the loudness and severity of tinnitus and can be a useful treatment for nonpulsatile chronic tinnitus